Father's and their children`s life goals in the context of Self-Determination Theory - Ewa Wojtowicz (University of Lower Silesia, 2013)
The aim of this study was to examine the similarities and differences in goals valuation in father's and children's life. According to the motivative Self-Determination Theory (Deci, Ryan, 2000) the aspirations were divided into two groups: external goals (i.e. finance, power, fame) and internal goals (i.e. affiliation and prosocial goals). The results suggest that teens, unlike their fathers, estimate higher affiliation goals. The report also shows (in both groups) relations between three categories of goals: prosocial, close relationships and self- acceptance.